Temporal trends in the prevalence and death of ischemic heart disease in women of childbearing age from 1990 to 2019: a multilevel analysis based on the Global Burden of Disease Study 2019 - Hu, Ben; Wang, Yan; Chen, Dong; Feng, Jun; Fan, Yinguang; Hou, Linlin (Frontiers in Cardiovascular Medicine, 2024)
Background: Our objective is to describe the current prevalence and death of ischemic heart disease (IHD) in women of childbearing age (WCBA) at the global, regional, and national levels and to analyze its temporal trends from 1990 to 2019.Methods: WCBA was defined as women aged 15-49 years. Estimates and 95% Uncertainty Intervals (UI) of IHD prevalence and death numbers for seven age groups were extracted from the 2019 Global Burden of Disease Study. The age-standardized prevalence and death rate (ASPR and ASDR) of IHD in WCBA was estimated using the direct age-standardization method. Joinpoint regression analysis was used to calculate average annual percent change (AAPC) to represent the temporal trends from 1990 to 2019. Results: Between 1990 and 2019, the global ASPR of IHD experienced a 3.21% increase, culminating in 367.21 (95% UI, 295.74-430.16) cases per 100,000 individuals. Conversely, the ASDR decreased to 11.11 (95% UI, 10.10-12.30) per 100,000 individuals. In 2019, among the five sociodemographic index (SDI) regions, the highest ASPR was observed in the high-middle SDI region, whereas the highest ASDR was found in the low-middle SDI region. Regionally, the Caribbean reported the highest ASPR (563.11 per 100,000 individuals; 95% UI, 493.13-643.03), and Oceania reported the highest ASDR (20.20 per 100,000 individuals; 95% UI, 13.01-31.03). At the national level, Trinidad and Tobago exhibited the highest ASPR (730.15 per 100,000 individuals; 95% UI, 633.96-840.13), and the Solomon Islands had the highest ASDR (77.77 per 100,000 individuals; 95% UI, 47.80-121.19).Importantly, over the past three decades, the global ASPR has seen a significant increase (AAPC = 0.11%, 95% Confidence Interval [CI]: 0.09-0.13; P < 0.001), while the ASDR has demonstrated a significant decreasing trend (AAPC = -0.86%, 95% CI:-1.11 to -0.61; P < 0.001). Air pollution, tobacco use, high systolic blood pressure, elevated body mass index, dietary risks, and high LDL cholesterol have been identified as the leading six risk factors for IHD-related deaths among WCBA in 2019.